Penilaian Sikap Pada Country Of Origin Image Terhadap Sustainability Dan Evaluasi Produk - Prakosa, Adhi (Universitas PGRI Yogyakarta, 2016)
Nowadays, marketers are faced with a higher level of consumers concern on social and environmental issues. Due to that reason, it is important for marketers to assess their business practices related to the country of origin products and concern of company on issue of environmental sustainability. The aim of this study is to examine differences in response of consumers towards attributes of environmental sustainability and product evaluation visits of their attitudes towards country of origin image. The dependent variable in this research is consumer perceptions on corporate social responsibility, transparency, and trust, where as the attitude of country of origin is the independent variable. The survey method is used in this study to evaluate hypothesis using one-way ANOVA analysis. As the result, it can be concluded that confidence of consumer in the company and the evaluation of the product will be different between consumers who have a high and a low country of origin image.